Concurrent changes in methyl jasmonate emission and the expression of its biosynthesis‐related genes in Cymbidium ensifolium flowers. Issue 4 (31st October 2014) - Huang, Mingkun; Ma, Cuiping; Yu, Rangcai; Mu, Lanling; Hou, Jia; Yu, Yunyi; Fan, Yanping
Abstract : Methyl jasmonate (MeJA) is one of most abundant scent compounds in Cymbidium ensifolium flowers. In this study, the emission of MeJA and its regulation mechanism were investigated. Our results showed that emission of MeJA in C. ensifolium flowers was controlled developmentally and rhythmically. It occurred in a tissue‐specific manner, and high MeJA emission was found in sepals and petals. A group of vital genes involved in the MeJA biosynthesis via the octadecanoid pathway were isolated from C. ensifolium flowers, including CeLOX, CeAOS, CeAOC and CeJMT . MeJA emission was at very low levels in unopened or half‐opened C. ensifolium flowers and reached its maximal level between day 4 and 6 and declined from day 7 to 10 postanthesis. The expression of CeLOX, CeAOS, CeAOC and CeJMT increased from day 1 to day 6, and then declined from day 7 to 10 postanthesis, corresponding to the change in MeJA emission. Moreover, the expression of CeLOX, CeAOS, CeAOC and CeJMT oscillated in a rhythmic manner could reach the maximum level between 8:00 h and 16:00 h, which coincided with the MeJA emission. The high level of MeJA emission in sepals and petals coincided with the high transcript levels. The results suggest that MeJA emission in C. ensifolium flower might be directly regulated at the transcription levels. Moreover, the recombinant protein of CeJMT could specifically catalyze the jasmonic acid to form the corresponding ester MeJA.